Comparing fluorescence-based cell-free assays for the assessment of antioxidative capacity of high-density lipoproteins. Issue 1 (December 2016) - Tsunoda, Fumiyoshi; Lamon-Fava, Stefania; Horvath, Katalin; Schaefer, Ernst; Asztalos, Bela
Abstract Background Population studies have shown an inverse association between high-density lipoprotein (HDL) cholesterol levels and risk of coronary heart disease (CHD). HDL has different functions, including the ability to protect biological molecules from oxidation. Our aim was to evaluate the performance of two fluorescence-based assays in assessing the antioxidative capacity of HDL. Methods We compared the antioxidative capacity of HDL with the phospholipid 2', 7'-dichlorodihydrofluorescein (DCF) assay and the dihydrorhodamine 123 (DHR) assay in controls and in subjects at increased risk of CHD, including subjects with established CHD, and subjects with elevated plasma triglycerides (TG), serum amyloid A (SAA), or myeloperoxidase (MPO) levels. Results The antioxidative capacity of HDL, as measured by the DCF assay, was significantly lower in both CHD and high-TG patients than in controls (p  < 0.001 andp  = 0.004, respectively). Interestingly, the mean antioxidative capacity of HDL in high-SAA subjects was significantly higher (p  < 0.03), while in high-MPO subjects was similar to controls. When the DHR assay was used we did not find differences in HDL's antioxidative capacity between CHD patients and controls but we found higher antioxidative capacity in high-SAA subjects compared to controls. Conclusions Only the DCF assay could detect significant differences in the antioxidative capacity of HDL between controls and CHD subjects. Practical use of both assays for the assessment of antioxidative capacity of HDL is limited by the large overlap in values among groups. The antioxidative activity of HDL in patients who have elevated SAA levels needs to be reassessed.